Los procedimientos jurídicos de protección de los derechos de la naturaleza desde una perspectiva constitucional en el Ecuador. - Polo, Aldair J. (2020)
The natures rights, come to take part of the regulations contained in the Constitution of the Republic of Ecuador since 2008, with a new concept of respect and protection of the ecosystem whose purpose is to establish that all ecuadorians enjoy a healthy and ecologically balanced environment. In the investigation it has been studied in depth the constitutional regulations determining the applicability form and the guarantee support granted by the State through the constitutional rights, over the respect for them which also focuses on finding solutions where the government has the obligation to allow public policies for prevention and protection of the environment. Through the field design an analysis of the current problem that the country is experiencing has been carried out regarding environmental damage, through the study of pollution rates and lack of attention by the authorities. Through the documentary design it has been possible to analyze the sentences issued by the judges of the instance according to the protection action, precautionary measures, as well as the decisions announced by judges of the Constitutional Court through the extraordinary protection action that are jurisdictional guarantees that protects the full enjoyment of the rights prescribed in the Constitution of the Republic of Ecuador. Through the interview with experts in the field results were obtained that helped determine a possible lack of application of legal procedures for full enjoyment of the rights of nature from a constitutional perspective. In this way this investigation has focused on determining whether the jurisdictional guarantees in terms of protection and care of the environment are effective for their defense obtaining favorable results through research methods.